Make-to-order, make-to-stock, or delay product differentiation?: a common framework for modeling and analysis - Gupta, Diwakar; Benjaafar, Saifallah; McMaster University, Michael G. DeGroote School of Business (My University, 1999)
Widespread increase in product variety and the simultaneous emphasis on shorter order delivery times and lower costs have increased the strategic importance of how much and where (in the production process) inventories should be maintained. In this article, we develop models that can be used to rapidly investigate a strategy in which product differentiation is delayed through product and process redesign, resulting in a two stage production process. Stage-1 produces undifferentiated items to stock to fill a buffer of size b. Stage-2 makes customized products from the stock of undifferentiated items after demand materializes. Subject to a service level constraint, we determine the optimal buffer size and the optimal workload allocation to the two production stages. This model captures both make-to order and make-to-stock situations as special cases. The former occurs when buffer size is zero and the latter when the entire workload is allocated to stage-1. Numerical experiments reveal that the degree to which postponement of differentiation is desirable depends mainly on the relative magnitudes of the system workload, the response time limit, and whether or not capacity can be flexibly allocated. These same parameters also determine the optimal size of the buffer. Surprisingly, we find that the optimal point of differentiation and buffer size are largely insensitive to the choice of holding, warehousing, and process redesign costs. The desirability of using delayed differentiation increases with product variety, and the relative magnitude of this increase is higher when greater product variety is accompanied by lower production volume of each item produced.
43 p. : ; Includes bibliographical references (p. 25). ; "April, 1999".
Keywords: Inventory control > Decision making Production planning > Decision making